Un/Certain Futures Rollen des Designs in gesellschaftlichen Transformationsprozessen - Förster, Marius; Hebert, Saskia; Hofmann, Mona; Jonas, Wolfgang (1dac307f-263a-47ea-b1d9-94d4a148ec5a, 2018)
A multi-Disciplinary View at Contingent Futures - Beyond the Placative Dualism of Design versus Disaster.